2013
DOI: 10.1186/1471-2458-13-38
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in HIV disease progression and treatment outcomes among HIV patients one year after starting antiretroviral treatment (ART) in Dar es Salaam, Tanzania

Abstract: BackgroundWe investigated gender differences in treatment outcome during first line antiretroviral treatment (ART) in a hospital setting in Tanzania, assessing clinical, social demographic, virological and immunological factors.MethodsWe conducted a cohort study involving HIV infected patients scheduled to start ART and followed up to 1 year on ART. Structured questionnaires and patients file review were used to collect information and blood was collected for CD4 and viral load testing. Gender differences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
32
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 19 publications
13
32
3
Order By: Relevance
“…Conflicting data have been reported on sex differences in CD4 cell count recovery after initiation of ART . We found no differences in CD4 cell count recovery after adjusting for baseline CD4 cell count and time from baseline CD4 cell count.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Conflicting data have been reported on sex differences in CD4 cell count recovery after initiation of ART . We found no differences in CD4 cell count recovery after adjusting for baseline CD4 cell count and time from baseline CD4 cell count.…”
Section: Discussioncontrasting
confidence: 94%
“…In contrast, other studies have reported a better immunological outcome in women . Two studies from Uganda and Tanzania showed that women are more likely to be virally suppressed on treatment, but the CD4 cell count change was the same as in men .…”
Section: Discussionmentioning
confidence: 82%
“…The adverse events relating to treatment was associated with young age in our series. This association corroborates what has been described in several studies [38] [39]. The reasons which are mostly mentioned in the non-optimization of ART in the young subject are the low compliance [40], the long duration of exposure [41], the inadequacy of dosage [42].…”
Section: Discussionsupporting
confidence: 90%
“…5 Another influence of sex was reported in Dar es Salam in Tanzania, where researchers determined that one-year after ART initiation, women have a better immunological response, with a high rate of undetectable virus load. 15 A high adherence to ART was associated with a decreased death rate, which has also been described elsewhere; however, 12 months of inpatient care increases the death rate. 1,5 The benefits of highly active ART in the treatment of HIV infection have been well described and include viral suppression, CD4 lymphocyte repletion, and durable reductions in HIV infection-related opportunistic diseases and death.…”
Section: Discussionsupporting
confidence: 64%